No evidence for human papillomavirus having a causal role in salivary gland tumors - Linnea Haeggblom; Ramona Gabriela Ursu; Leila Mirzaie; Tove Attoff; Caroline Gahm; Lalle Hammarstedt Nordenvall; Anders Näsman (BMC, 2018)
Abstract Background Salivary gland malignancies are a very heterogeneous group of cancers, with histologically > 20 different subtypes, and prognosis varies greatly. Their etiology is unknown, however, a few small studies show presence of human papillomavirus (HPV) in some subtypes, although the evidence for HPV having a causal role is weak. The aim of this study was to investigate if HPV plays a causal role in the development of different parotid salivary gland tumor subtypes. Methods DNA was extracted from 107 parotid salivary gland formalin fixed paraffin embedded tumors and 10 corresponding metastases, and tested for 27 different HPV types using a multiplex bead based assay. HPV DNA positive tumors were stained for p16INK4a overexpression by immunohistochemistry. Results One of the 107 malignant parotid salivary gland tumors (0.93%) and its corresponding metastasis on the neck were positive for HPV16 DNA, and both also overexpressed p16INK4a. The HPV positive primary tumor was a squamous cell carcinoma; neither mucoepidermoid nor adenoid cystic tumors were found HPV positive. Conclusions In conclusion, HPV DNA analysis in a large number of malignant parotid salivary gland tumors, including 12 different subtypes, did not show any strong indications that tested HPV types have a causal role in the studied salivary gland tumor types.